BISMUTH IN FERROMANGANESE NODULES AND ORE CRUSTS OF THE OCEAN - Baturin G.N.; Oreshkin V.N. (My University, 1988)
The aim of the work reported was to obtain representative data on the concentration and distribution of bismuth in ferromanganese nodules and ore crusts and to establish its relationships to their principal ore-forming elements, i.e., manganese and iron. The material studied was collected on 43rd and 48th cruises of the R/V Vityaz' in the Pacific. In all, 83 samples were analyzed including 21 ferromanganese nodules (whole samples), 27 outer shells of nodule, seven mineralized nodule cores and 28 ore crusts on volcanic and compact sedimentary rocks. Study materials, methods and results are discussed.